THE EXISTENCE OF COMMUNITY SPACES OUTSIDE THE FLAT BLOCK AFFECTED BY ACTIVITIES OF LOWINCOME RESIDENTS - Ratna Darmiwati (Journal of Architecture&ENVIRONMENT, 2020)
Culture as a system includes ideas, concepts, rules, and meanings. It underlies the expression of human life and a system of common sense as a result of the social process. It emphasizes an abstract thing rather than concrete ones. Behavior as cultural expressions deals with the relationship between one another. The resident's social activities cannot be implemented as desired which causes them to find new places that can meet the user's behavior and culture. If the behavior and community space used are appropriate, they will continue to develop their lives in the same place. Furthermore, they can attract people from other blocks to join.The process of utilizing existing facilities and treating nature according to the social system of low-income users need environmental adaptation. This study explores the existence of community spaces outside the building in a flat environment related to the behavior and culture of residents as users. This assessment is based on community togetherness in community spaces, either planned or unplanned.The research method used is Descriptive-Qualitative-Exploratory, with interviews of selected respondents. The number and the origin of residents who gathered in the community with various activities are the indications of the suitability of the community space. Low-income residents generally meet somewhere with a variety of diverse needs. The existence of planned community space is used maximally. This space is used by many people for various needs. For low-income residents, this place can meet their interests simultaneously. It means that the place will be used based on the functions, the fragmentation of togetherness, focused activities, consistency, the user's character, affordability, and environment order.